2011
DOI: 10.1515/jpem.2011.405
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors associated with low bone mineral content in underprivileged premenarchal Indian girls

Abstract: Low adolescent peak bone mass is associated with bone problems in adulthood. Our aim was to assess underprivileged premenarchal Indian girls for low bone mineral content and to study the infl uence of anthropometric, lifestyle factors on bone health. Data on anthropometry, diet, lifestyle, total body bone mineral content (TBBMC), bone area, bone mineral density, and biochemical parameters [parathyroid hormone, vitamin D (25OH-D), calcium, and zinc] were assessed in 214 premenarchal girls (8 -12 years). Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…These results are in line with other studies 8 9 11. Our study also showed a negative correlation between serum 25OHD and intact serum PTH concentrations, as has been observed in other cross-sectional studies 2 10 20 21…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in line with other studies 8 9 11. Our study also showed a negative correlation between serum 25OHD and intact serum PTH concentrations, as has been observed in other cross-sectional studies 2 10 20 21…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies on Indian children and adolescents have found that they have lower bone mass than their Caucasian counterparts 7 8. Although India is a sun-rich country, there are many reports suggesting low vitamin D concentrations in Indian adolescents 9 10.…”
Section: Introductionmentioning
confidence: 97%
“…in 2011. It showed a prevalence of 34.2% of Vitamin D.[ 47 ] Another school-based study done by Kapil et al . in 2017 on 1222 school children aged 6–18 years in Kangra and Kullu districts of Himachal Pradesh, showed the prevalence of 81% and 80% respectively.…”
Section: Magnitude Of Vitamin D Deficiency In Indiamentioning
confidence: 99%
“…There is scant information on prevalence of asymptomatic vitamin D deficiency in prepubertal age group from India, and even less on symptomatic deficiency. A study from Pune in this age group reported a mean serum 25-hydroxy vitamin D (25(OH)D) level of 24.6 ng/mL with 34.2% prevalence of vitamin D deficiency [6], while a higher prevalence in school children has been reported from Delhi by Marwaha, et al [7]. Limited evidence indicates that the risk of vitamin D deficiency may be lower in this age group as compared to pre-school children [8].…”
Section: Do Healthy Pre-pubertal Girls Need Supplementation With Vitamentioning
confidence: 88%